Mastering integral methods: a systematic approach - Foo, Fong Yeng; Ng, Set Foong; Ahmad, Shamsatun Nahar; Mahat, Aishah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2026)
Integration is a fundamental concept in calculus that plays a central role in mathematics, science, engineering, and many applied fields. Mastery of integration techniques is therefore crucial for students seeking a deeper understanding of calculus. This book is designed to present the techniques of integration in a clear, systematic, and accessible manner. It begins with the concept of the indefinite integral and introduces the basic rules required to evaluate elementary integrals, including algebraic, exponential, and trigonometric functions. These foundational topics prepare the reader for more advanced methods. Subsequent chapters develop essential techniques such as substitution and integration by parts, emphasizing their conceptual foundations and practical use. The connection between definite integrals and antiderivatives is established through the First Fundamental Theorem of Calculus. The book then addresses more specialized integration methods, including integrals involving trigonometric functions, trigonometric substitutions, and rational functions. These techniques are systematically introduced such that the readers can handle a wide range of integrals encountered in coursework and applications. Throughout the text, the progression of topics is arranged to build gradually from basic principles to more sophisticated techniques. This book is suitable for students in introductory and intermediate calculus courses, as well as for self-learners seeking a structured and comprehensive review of integration techniques. It is hoped that this text will serve not only as a practical guide for evaluating integrals, but also as a resource that fosters a deeper appreciation of integration as a powerful and unifying tool in mathematics.